Compensatory growth and production economics of Silver pompano, Trachinotus blochii (Lacepede, 1801), fingerlings stunted by feed and space deprivation - P. P., Suresh Babu; A., Anuraj; M. T., Shilta; Ebeneezar, Sanal; P., Shinoj; K., Raghu Ramudu; N. D., Praveen; N. G., Vaidya; Pal, Mahendra; I., Boby; K. K., Anikuttan; A., Gopalakrishnan (Frontiers in Marine Science, 2023)
The effect of stunting by feed and space deprivation on compensatory growth (CG) in Silver pompano, Trachinotus blochii was investigated. A commercial pellet feed (45 % protein and 10 % fat) was fed two times a day, throughout the entire experiment. The 270 days experiment consisted of an initial 60 days stunting and a 60 days post-stunting phase carried out in 4 × 2 × 2 m 3 galvanized iron (GI) cages, and 150 days grow-out phase carried out in 3 m diameter circular GI cages. During the stunting phase, the normal fish (in triplicates) were stocked at lower stocking density (17.5 fish / m 3 ) and fed at 10 % of body weight (BW), while stunted fish (one replication) were stocked at about three times higher stocking density (56 fish / m 3 ) and fed at a three times lower feeding rate (3 % of BW)., The stunted and normal fish were reared in triplicates during the post-stunting phase, at uniform stocking density (15 fish / m 3 ) with feeding at a higher rate (10 % of BW) for stunted fish and normal feeding rate (8 % of BW) was adopted for normal fish.During the grow-out stage, each replication from the post-stunting phase was shifted to 3 m circular cages with the same feeding rates. The lag in growth in stunted fish (5.56 g against 9.43 ± 0.13 g of normal) during the stunting phase was compensated during the post-stunting phase (36.88 ± 2.23 g against 38.13 ± 1.48 g of normal) by higher feeding rate. There were no significant (p > 0.05) difference in final harvest, biometry, morphometry, dressing yield, carcass nutritional composition and serum biochemical markers at the end of grow-out stage. Because of the significant difference (p < 0.05) in the total feed provided (5.2 kg for stunted fish against 22.8 kg for normal fish) and the lesser unit cost for the production of stunted fingerling (USD 0.087 for stunted fish against USD 0.106 for normal), the farming of stunted fish brought about a higher net operational revenue and benefit : cost ratio.